Charting a Programmatic Roadmap for Sexual Minority Groups in India - World Bank (Washington, DC, 2014)
Discrimination and stigma are constant companions in the life of the rainbow people. Apart from the demand for decriminalization, the main issues that confront the community are discrimination and violence, recognition of alternative family structures, adoption and property rights, and access to social security measures including identity documentation, welfare schemes, and education and health services. In order to establish a realistic plan for their inclusion into state provided services and liberties, it was important to understand what prevents them from doing so at this time, and to develop a carefully crafted roadmap for actions that the State, community and other stakeholders can program into their day-to-day work. Sexual minorities have fought a long battle against discrimination. Criminalization of Hijra and homosexuals took place during the colonial period and Lord Macaulay drafted the now infamous section 377 of the Indian Penal Code (IPC) according to the law, voluntary carnal intercourse against the order of nature could be punished by imprisonment. Laws such as section 377 have long been removed in most western democracies, although they persist in many post-colonial countries in Asia and Africa. In 2009, the Delhi High Court also read down the law, legalizing same sex consensual homosexual activities between adults. This judgment is unfortunately now challenged at the Supreme Court of India which is currently hearing the arguments of either side. The decriminalization of the community remains a fundamental issue which needs resolution if the community is to attain its rightful due. Continued advocacy on the part of the community and education of its people in the implications of the 2009 High Court judgment are important steps.